2021
DOI: 10.1007/s00018-021-03769-y
|View full text |Cite
|
Sign up to set email alerts
|

Apical-basal polarity regulators are essential for slit diaphragm assembly and endocytosis in Drosophila nephrocytes

Abstract: Apical-basal polarity is a key feature of most epithelial cells and it is regulated by highly conserved protein complexes. In mammalian podocytes, which emerge from columnar epithelial cells, this polarity is preserved and the tight junctions are converted to the slit diaphragms, establishing the filtration barrier. In Drosophila, nephrocytes show several structural and functional similarities with mammalian podocytes and proximal tubular cells. However, in contrast to podocytes, little is known about the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…The apical and basal plasma membrane domains are defined by the junctional zone and SD/lacunar channel diaphragms in mammalian podocytes and fly nephrocytes, respectively. Moreover, apical-basal polarity in both cell types is governed by the same classical polarity proteins, which have been found to play key roles in SD assembly, maintenance and endocytosis ( Michgehl et al, 2017 ; Heiden et al, 2021 ) ( Figure 2 and Table 1 ).…”
Section: The Importance Of Apical-basal Polarity For Slit Diaphragm F...mentioning
confidence: 98%
See 1 more Smart Citation
“…The apical and basal plasma membrane domains are defined by the junctional zone and SD/lacunar channel diaphragms in mammalian podocytes and fly nephrocytes, respectively. Moreover, apical-basal polarity in both cell types is governed by the same classical polarity proteins, which have been found to play key roles in SD assembly, maintenance and endocytosis ( Michgehl et al, 2017 ; Heiden et al, 2021 ) ( Figure 2 and Table 1 ).…”
Section: The Importance Of Apical-basal Polarity For Slit Diaphragm F...mentioning
confidence: 98%
“…This transformation requires (re-)localization of many apical junction proteins to the basal side of the podocyte, where they are gradually replaced by the SD ( Ichimura et al, 2017 ). Even though nephrocytes are not derived from epithelial progenitor cells, they do show the distinct apical-basal polarity ( Heiden et al, 2021 ). The apical and basal plasma membrane domains are defined by the junctional zone and SD/lacunar channel diaphragms in mammalian podocytes and fly nephrocytes, respectively.…”
Section: The Importance Of Apical-basal Polarity For Slit Diaphragm F...mentioning
confidence: 99%
“…These results suggest that apical polarity determinants are important for endocytosis and slit diaphragm homeostasis. Basolateral polarity regulators are also critical for mammalian nephrin homolog Sns localization in Drosophila ( 116 ). Basolateral polarity proteins- Discs large, Scribble, Lethal giant larvae, and Par-1 are important for normal endocytic trafficking of slit diaphragm proteins including zonula occludens-1 (ZO-1), which was confirmed by colocalization with early endosome Rab5, recycling endosome Rab7, and late endosome Rab11, respectively.…”
Section: Endocytosis In Podocyte Homeostasis and Diseasementioning
confidence: 99%
“…Disturbance of slit diaphragm formation as well as of endocytic receptors and proteins involved in the endocytosis machinery have been reported to reduce endocytosis (Soukup et al, 2009;Weavers et al, 2009;Zhuang et al, 2009;Zhang et al, 2013a;Hochapfel et al, 2017;Weide et al, 2017;Hermle et al, 2018;Kampf et al, 2019;Troha et al, 2019). In order to test, whether PI(4,5)P2 is essential for endocytosis in nephrocytes, we quantified the accumulation of secreted ANP-2xGFP (Heiden et al, 2021) which is secreted into the hemolymph, filtrated by nephrocytes and taken up by endocytosis. Indeed, downregulation of Sktl in nephrocytes, reducing PI(4,5)P2 levels, resulted in a strong decrease of ANP-2xGFP accumulation in nephrocytes, consistent with impaired endocytosis (Fig.…”
Section: Decreased Pi(45)p2 Levels Impair Endocytosis In Nephrocytesmentioning
confidence: 99%
“…Furthermore, we recently showed, that regulators of classical apical-basal polarity in epithelia are partly localized to slit diaphragm complexes (Heiden et al, 2021). Knockdown studies revealed that apical polarity regulators, such as Crumbs/Stardust and the PAR/aPKC complex as well as the basolateral polarity determinants Scribble/Lethal (2) giant larvae and PAR-1 are essential for slit diaphragm formation and -at least some of them -for endocytosis (Hochapfel et al, 2017;Weide et al, 2017;Heiden et al, 2021).…”
Section: Introductionmentioning
confidence: 99%